Процесс снятия фаски резкой в штампах для усиления сварных соединений в сельском машиностроении - Хорольський, В. Л.; Шлик, С. В.; Khorolskyi, Vladimir; Shlyk, Sergii (КНТУ, 2015)
Рассмотрены основные прогрессивные методы разделки скосов и снятия фасок на листовых заготовках перед сваркой. Определено напряженно-деформированное состояние системы «нож-заготовка» в штампах с симметричным нагружением и штампах со скользящим пуансоном. Осуществлен выбор более рациональной схемы резки по наименьшим нагрузкам, действующим на инструмент. Розглянуто основні прогресивні методи утворення скосів і зняття фасок на листових заготовках перед зварюванням. Визначено напружено-деформований стан системи «ніж-заготовка» в штампах з симетричним навантаженням і штампах з ковзаючим пуансоном. Здійснено вибір більш раціональної схеми різання по найменшим навантаженням, що діють на інструмент. The purpose of the work is to carry out the calculation of the stress-strain state of the "knife-bar" in the process segments using the above two schemes, and choose a more rational scheme. In this work the optimal parameters of the models parts finite element analysis, rational scheme forming edge selected on the basis of the smallest loads acting on the tool, set the effect of the geometry and direction of movement of the cutting parts of the above schemes on the quality of the bevel. The calculations were performed using the software package ANSYS / LS-DYNA. For this calculation schemes were drawn up models to determine the optimum parameters of parts models and types of contact interaction. Based on the equivalent stress diagrams and graphs of the voltage at the cutting edges concluded higher loads acting on the cutting edge in the case of circuits with unbalanced loading. It has been found that the use of stamps with the sliding punch avoids the formation of burrs on the workpiece and the corrugations characteristic circuit with an asymmetric loading.
Процес зняття фаски різанням у штампах для посилення зварювальних з’єднань у сільському машинобудуванні
The process of chamfering sharp in dies for strengthening the welded joints in the agricultural machinery
Keywords: резка; штамп; напряженно-деформированное состояние; скользящий пуансон; метод конечных элементов; різання; напружено-деформований стан; ковзаючий пуансон; метод скінченних елементів; cutting stamp; stress-strain state; the sliding punch; finite element method